Archaeology of dance in Java interpreting the past through iconography - Iyer, Alessandra
Alessa Iyer traces reliefs of the Siva Temple at the Prambanan Complex in Indonesia to reconstruct dance movements of an ancient art form.
Keywords: Dance; Art; Idols and images